Evaluation of In Vitro Antioxidant Activity of Ethanolic Extract from Vallaris solanacea Leave - Pitchaimuthu Pandian (Journal of Global Pharma Technology, 2021)
Several methods employed in evaluating antioxidant activities on varied samples gives varying results depending on the specificity of the free radical or oxidant used as a reactant. This study investigated the antioxidation /radical scavenging properties since ethanolic extraction on Vallaris solanacea leaves. Antioxidant capacity on Vallaris solanacea leaves were evaluate near measuring a DPPH photometric assay, Superoxide radical scavenging activities, Iron chelating activities, Hydroxyl radical scavenging activity, Nitric oxide radical scavenging activities, Total antioxidant activities, Ferric Reducing Ability Power (FRAP) assay, full phenol content overall flavonoids content. A concentration was 125, 250, 500, 1000 μg/ml. The standard was used according to their methods. All values are expressed for mean ± SEM for three determinations with percentage of activity (±SEM) of IC50 values. The result revealed that DPPH as 625μg/ml, Superoxide radical scavenging as 459μg/ml, Iron chelating activity as 639μg/ml, Hydroxyl radical scavenging as 556μg/ml, Nitric oxide original scavenging as 683μg/ml, Total antioxidant as 638 μg/ml, FRAP as 543μg/ml and the total phenolic , flavonoids content was 3.980±0.007 and 2.651±0.077. The findings from the study reveal that the antioxidative potentials of Vallaris solanacea leaves of ethanolic extract and could serve as free radical inhibitors, phenolic and flavonoids as possibly acting as principal antioxidantsKeywords: Vallaris solanacea antioxidant, phenols, flavonoids, free radical.